DEVELOPMENT OF PERFORMANCE IMPROVEMENT OF MSMEs IN LOYOK VILLAGE SIKUR DISTRICT EAST LOMBOK REGENCY BASED ON SWOT ANALYSIS - Muhamad Yusup; Triana Lidona Aprilani (IQTISHADUNA, 2021)
This study aims to development a SWOT analysis and strategies for improving the performance of MSMEs based on a SWOT analysis. This type of research is descriptive which describes the strengths, weaknesses, opportunities and threats faced by MSMEs in Loyok Village, Sikur District, East Lombok Regency. The type of data used is primary data and secondary data collected by means of documentation, interviews, and in-depth interviews. The research population is all MSMEs actors who are craftsmen, ranging from making baskets, jars, bamboo fans, hats, to skewers and bags whose prices vary. The sample is determined by proportional random sampling. Data were analyzed qualitatively and SWOT analysis. The results show that the strengths of MSMEs are: the availability of raw materials and labor at relatively cheap prices, the quality of the product is very good, the weaknesses of MSMEs are: the number of qualified workers is still low, product designs are less innovative and market information limited opportunities, the opportunities they have are: obtaining capital assistance in the form of soft loans from Village-Owned Enterprises, attention from the government, especially training and assistance and the threats faced by MSMEs are: intense competition and low economic conditions. Four strategies are used to improve the performance of MSMEs based on the results of the SWOT analysis, namely: first, the SO strategy by maintaining product quality by utilizing the assistance of Village-Owned Enterprises and government training, both the WO strategy in compiling online marketing programs and increasing product design innovation and creativity, three strategies ST optimizes the availability of raw materials and relatively cheap labor to win the competition and the four WT strategies increase product design creativity and seek new market share.